Biotreatment for effective degradation and decoloration of textile effluent using novel spore forming Bacillus sp - Shanmugaraja2, V.Prabakaran3, M.Vigneeswaran1*, B. Govindarajan1, K. (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Bacillus sp, an effective spore forming organism revealed a result in degrading and decolorizing the textile effluent, which was one of the major environmental pollution in modern world. This work mainly focused in tune with the decolaration of textile effluent sample collected from Salem district. Textile effluent samples were analysed for heavy metals (Nickel and Zinc) in AAS (Atomic absorption spectrometry). Further the soil samples collected from different areas of contaminated with effluent was enriched, isolated and characterized and PCR amplified for species identification and confirmed as Lysini bacillus sphaericus. The genus Bacillus, which was beneficial for the degradation of toxic constituents present in the textile effluents, further it was also confirmed by the decolorization bioassay with least value of the final color. The continued development and application of biotechnologies for the biodegradation is limited primarily by physical factors such as pH, temperature and substrate concentration. Biotreatment offers a cheaper and environmentally friendlier alternative for colour removal in textile effluents. The ubiquitous nature of bacteria makes them invaluable tools in effluent biotreatment. Decoloration of dye from effluent samples, were monitored for 4-8 days by spectrometric observation.